Bioenergy life cycle assessment and management in energy generation. Issue 1 (January 2018) - Taylan, Osman; Kaya, Durmus; Bakhsh, Ahmed A; Demirbas, Ayhan
Bioenergy is an effective energy form used by developing countries. It covers about 38% of the energy consumed primarily obtained from the biomass in about 13% of the world. Due to the energy production costs, much attention has currently been paid on alternative bioenergy sources in the developing countries. Biofuels may be used instead of fossil fuels to produce power, heat, and/or some chemicals. Its production with local resources suggests a reproducible alternative streamlining the economic and social improvement in developing countries, in case the bioenergy projects are established economically viable and well planned with local cooperation. Biofuels are important resources which can take place with fossil-based fuels. Generally speaking, biofuels offer several benefits such as the reduction of greenhouse gas emissions, regional social and structural development, sustainability in energy provision, and agricultural development. In this study, a life cycle analysis of a full-scale biogas plant was conducted. In the life cycle analysis, the ecological effects of the biogas process, the by-products from the biogas production, and the cogeneration unit where the electricity generation is performed are evaluated quantitatively according to the ISO 14040. The functional unit of the plant was designed for 30 tons per day big cattle manure, 5 tons per day poultry manure, and 15 tons per day cheese whey of industrial biogas plant.